PERAN POSTULAT KEBERLANJUTAN USAHA (GOING CONCERN) DALAM AKUNTANSI: KAJIAN TEORI, IMPLEMENTASI, DAN IMPLIKASINYA TERHADAP PELAPORAN KEUANGAN - Aprita Ravenna Ginting; Cindy Aulia Rusli; Dea Natalia Sembiring; IMAN SUYAKIN DAELI; Wanda Dea Khairani; Jufri Darma (Universitas Logistik dan Bisnis Internasional, 2026)
The going concern postulate is one of the fundamental concepts in accounting theory, which assumes that a company will continue its operations for the long term. This article aims to discuss the theoretical concept of going concern as an essential postulate in accounting, explain its application in financial reporting and auditing practices, and examine its impact on the reliability of financial statements. The study adopts a literature review method by analyzing various sources, including accounting standards such as PSAK No. 1 and IAS 1, as well as relevant academic studies. The results of the review indicate that the application of the going concern postulate plays a significant role in maintaining the consistency and credibility of financial statements. The assessment of this assumption requires professional judgment concerning a company’s financial condition, cash flows, and business prospects. If the going concern assumption cannot be maintained, it may lead to changes in the basis of financial statement preparation and reduce stakeholders’ trust. Therefore, a comprehensive understanding of the going concern postulate is essential to promote transparency and accountability in financial reporting.